ESD in industry - present and future. (September 2015) - Smallwood, Jeremy
Abstract: ElectroStatic Discharge (ESD) has been a recognized source of damage to unprotected electronic components and assemblies in electronic system manufacture since around 1980. Since then, manufacturers handling ESD Sensitive components (ESDS) have set up ESD Protected Areas (EPAs) for the purpose, and internationally recognized ESD control standards supported by standard test methods and procedures have been developed. Meanwhile, development of ESDS device on-chip protection has continued. This paper examines the trends in ESDS component sensitivity, and the need for development of ESD control in EPAs. It asks if ESD protection is well understood by those in industry who have to implement it, and whether there is adequate education and research in the subject. Finally, it comments on whether the electronics industry and other industry areas where reliable and effective electrostatic control is required could learn from each other's practices.